Kualitas Isi dan Kalimat Efektif pada Teks Berita di Website Detikjabar Edisi Februari 2024 sebagai Bahan Bacaan dan Sumber Informasi bagi Mahasiswa - Adhwa Farah Yosinta; Anton April Laksono; Intana Aura Izza; Wahidah Mustaqimah; Wanda Sukmawati; Asep Purwo Yudi Utomo; Galih Suci Pratama (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Ineffective sentences are sentences that have several words that are difficult to understand. This research is motivated by the writers in the preparation of sentences in news texts that are not in accordance with linguistic rules. This research aims to identify the use of effective sentences in online news texts, with a focus on the article "It's Time to Clean up APKs in Bandung City" found on the February 2024 Edition of the Detikjabar Website. This analysis aims to analyze ineffective sentences in the article and produce more effective sentences, in accordance with linguistic rules. The research method used is a qualitative descriptive approach, with a syntactic theoretical approach. The results showed several ineffective sentences found in the news text, such as the use of less formal words and typos. The sentence improvements offered aim to improve clarity and conformity with correct linguistic rules. It is hoped that this knowledge can help readers understand the importance of effective sentences in news texts and avoid language errors in writing. The benefits of this analysis include a better understanding of the correct use of language in the context of online news, both in academic and non-academic activities.